Incidence, clinical profile and maternal–fetal mortality in pregnancies complicated by obstructed labor - Sultana, Jesmin; Tasrin, Liza; Ara, Shamim; Mehbin, Marzia; Nancy, Chyochyo; Sultana, Nargis (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Obstructed labour is a significant cause of maternal and fetal morbidity and mortality, particularly in low-resource settings. This study aimed to assess the incidence, clinical profile, and maternal–fetal outcomes in pregnancies complicated by obstructed labour. Methods: This cross-sectional prospective study was conducted in the Department of Obstetrics and Gynaecology, Sher-e-Bangla Medical College Hospital, Barisal, Bangladesh, from July 2008 to June 2009. This study included 100 patients admitted with obstructed labour across all units of the Obstetrics and Gynaecology Department at Sher-e-Bangla Medical College Hospital. Results: Most patients were aged 21–30 years (54%) and primigravida (62%). Cephalopelvic disproportion (42%) and persistent occipito-posterior position (28%) were the main causes of obstruction. At admission, 72% were in the second stage of labour, and 54% had labour lasting 25–48 hours. Caesarean section was the predominant mode of delivery (85%). Hypertonic uterine contractions were noted in 46%. Clinically, 59% had raised temperature, 66% had moderate anaemia, and 56% had moderate dehydration. Fetal assessment revealed abnormal or absent heart sounds in 86%, and 91% had meconium-stained liquor. At birth, 43% were stillborn, 38% asphyxiated, and 19% healthy. Genital tract injuries occurred in 27%, predominantly vaginal lacerations (14%). Wound infection (37%), pyrexia (32%), and postpartum haemorrhage (26%) were the main maternal morbidities. Maternal mortality was 3%, while 44% were healthy at follow-up. Conclusions: Obstructed labour is associated with substantial maternal and fetal morbidity and mortality. Early recognition, timely referral, and appropriate obstetric intervention are essential to improve outcomes.